Reticular three-dimensional 3d–4f frameworks constructed through substituted imidazole-dicarboxylate: syntheses, luminescence and magnetic properties study. Issue 2 (18th November 2014) - Feng, Xun; Feng, Yu-Quan; Chen, Jun Jing; Ng, Seik-Weng; Wang, Li-Ya; Guo, Jin-Zhong
Abstract : Series of heteronuclear metal organic frameworks (HMOF) combination of lanthanide and Zn/Co ions based on a rigid substituted imidazoledicarboxylic acid ligand have been successfully isolated and characterized systematically. Abstract : A family of heteronuclear metal organic frameworks (MOFs) using lanthanide and transition metal ion based on a rigid ligand of substituted imidazoledicarboxylic acid, namely, [Ln2 Zn2 (μ3 -Hmimda)2 (μ3 -mimda)2 ·4H2 O] n · mn H2 O, Ln = Nd, m = 2 (1 ), Ln = Ho, m = 3 (2 ), Ln = Er, m = 2 (3 ), Ln = Yb, m = 3 (4 ), [Tb2 Co2 (μ3 -Hmimda)2 (μ3 -mimda)2 ·4H2 O] n ·2 n H2 O